A Reversible and Selective Inhibitor of Monoacylglycerol Lipase Ameliorates Multiple Sclerosis1. Issue 50 (8th October 2014) - Hernández‐Torres, Gloria; Cipriano, Mariateresa; Hedén, Erika; Björklund, Emmelie; Canales, Ángeles; Zian, Debora; Feliú, Ana; Mecha, Miriam; Guaza, Carmen; Fowler, Christopher J.; Ortega‐Gutiérrez, Silvia; López‐Rodríguez, María L.
Abstract Monoacylglycerol lipase (MAGL) is the enzyme responsible for the inactivation of the endocannabinoid 2‐arachidonoylglycerol (2‐AG). MAGL inhibitors show analgesic and tissue‐protecting effects in several disease models. However, the few efficient and selective MAGL inhibitors described to date block the enzyme irreversibly, and this can lead to pharmacological tolerance. Hence, additional classes of MAGL inhibitors are needed to validate this enzyme as a therapeutic target. Here we report a potent, selective, and reversible MAGL inhibitor (IC50=0.18 μM) which is active in vivo and ameliorates the clinical progression of a multiple sclerosis (MS) mouse model without inducing undesirable CB1‐mediated side effects. These results support the interest in MAGL as a target for the treatment of MS.